Báo cáo Tiếp thu, giải trình và chỉnh lý dự thảo Nghị quyết về hoạt động chất vấn tại Kỳ họp thứ 7 - Ủy ban Thường vụ Quốc hội (2024)
Toàn văn Báo cáo Tiếp thu, giải trình và chỉnh lý dự thảo Nghị quyết về hoạt động chất vấn tại Kỳ họp thứ 7.